2022
DOI: 10.1051/0004-6361/202244239
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-spherical superclusters

Abstract: Context. Superclusters are systems with varied properties and varied fractional overdensities. Their dynamical state evolves under the influence of two components: dark energy and gravitational force. The dominant component at any spatial location and cosmic epoch is determined by the total mass and the local overdensity of the system. However, generally the dynamical state of superclusters is poorly known. Aims. We study properties of superclusters and select a sample of quasi-spherical superclusters, the dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…The topological analysis of the shape of superclusters may explain this phenomenon more clearly. Recently, Bag et al (2023) found that large superclusters with volumes 10 4 Mpc 3 tend to be more filamentary, and Heinämäki et al (2022) found that the low-luminosity, small, poor, and lowmass end of superclusters has pancake-type shapes, while only a handful exhibit exceptionally spherical shapes. The supercluster environment weakly affects the evolution of clusters.…”
Section: Discussionmentioning
confidence: 99%
“…The topological analysis of the shape of superclusters may explain this phenomenon more clearly. Recently, Bag et al (2023) found that large superclusters with volumes 10 4 Mpc 3 tend to be more filamentary, and Heinämäki et al (2022) found that the low-luminosity, small, poor, and lowmass end of superclusters has pancake-type shapes, while only a handful exhibit exceptionally spherical shapes. The supercluster environment weakly affects the evolution of clusters.…”
Section: Discussionmentioning
confidence: 99%